Albania : Fourth Review Under the Extended Arrangement and Request for Modification and Waiver of Applicability of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Albania's Fourth Review Under the Extended Arrangement and Request for Modification and Waiver of Applicability of Performance Criteria (PC). Economic recovery is under way, but growth remains below potential. The low oil price is expected to have a muted effect on growth and on the balance of payments, as pass-through is weak and Albania is only a small net oil exporter. The program is on track. All end-December 2014 and continuous PCs and most indicative targets were met, with comfortable margins. The IMF staff supports the completion of the Fourth Review under the Extended Arrangement, as well as the modification and waiver of applicability of PC.